Assessing first semester diploma students' digital capabilities, self-regulation and perceptions on computing-based course: a post-covid study / Ling-Ling Ung, Nasrah Naharu and Gloria Jennis Tan - Ung, Ling-Ling; Naharu, Nasrah; Tan, Gloria Jennis (Faculty of Information Management, 2023)
This study investigated the computing usage, capabilities, and selfregulation of first-semester diploma students who have taken online classes since the COVID-19 outbreak in 2020. The research employed a purposive sampling method, meaning the sample was selected based on predefined criteria. The data collection tool was a survey form composed of closed-ended questions, with responses measured using a five-point Likert scale. The collected data were then descriptively analyzed using the IBM Statistical Package for the Social Sciences (SPSS) version 27. This analysis involved calculating percentages, mean scores, and standard deviations (SD). The study aimed to identify areas where students may require support and instruction to develop the digital skills necessary for success in today’s society. The findings also provided insights into the effectiveness of computing-based courses and suggested ways in which they can be modified to better meet the needs of students. By addressing these research aims, this study contributes to our understanding of the role of technology in education. It provides a foundation for future research in this area.